Radiological Mapping of Post-Disaster Nuclear Environments Using Fixed-Wing Unmanned Aerial Systems: A Study From Chornobyl - Connor, Dean T.; Wood, Kieran; Martin, Peter G.; Goren, Sevda; Megson-Smith, David; Verbelen, Yannick; Chyzhevskyi, Igor; Kirieiev, Serhii; Smith, Nick T.; Richardson, Tom; Scott, Thomas B. (Frontiers in Robotics and AI, 2020)
In the immediate aftermath following a large-scale release of radioactive material into the environment, it is necessary to determine the spatial distribution of radioactivity quickly. At present, this is conducted by utilising manned aircraft equipped with large-volume radiation detection systems. Whilst these are capable of mapping large areas quickly, they suffer from a low spatial resolution due to the operating altitude of the aircraft. They are also expensive to deploy and their manned nature means that the operators are still at risk of exposure to potentially harmful ionising radiation. Previous studies have identified the feasibility of utilising unmanned aerial systems (UASs) in monitoring radiation in post-disaster environments. However, the majority of these systems suffer from a limited range or are too heavy to be easily integrated into regulatory restrictions that exist on the deployment of UASs worldwide. This study presents a new radiation mapping UAS based on a lightweight (8 kg) fixed-wing unmanned aircraft and tests its suitability to mapping post-disaster radiation in the Chernobyl Exclusion Zone (CEZ). The system can is capable of continuous flight for more than one hour and resolving small scale changes in dose-rate in high resolution (sub-20 m). It is envisaged that with some minor development, these systems could be utilised to map large areas of hazardous land without exposing a single operator to a harmful dose of ionising radiation.